Simian virus 40 (SV40)-transgenic mice that develop tumors are specifically tolerant to SV40 T antigen (The Rockefeller University Press, 1987)
The ability to mount an immune response to simian virus 40 (SV40) T antigen was evaluated using mice from two distinct SV40 transgenic lines derived from injection of the same gene construct. Our studies demonstrate functional immune tolerance to SV40 T antigen in a SV40 transgenic line that consistently develops tumors of the choroid plexus by 7 mo of age. Antibodies to SV40 T antigen are undetectable in the serum of these animals; furthermore, mice from this line are unable to generate SV40-specific CTL after primary or secondary immunization with the virus, although they mount a normal CTL response to vaccinia virus when appropriately immunized. In contrast, we find that mice from a second transgenic line of low tumor incidence can mount a humoral response to SV40 T antigen, and upon immunization they generally respond with a vigorous cytotoxic T cell response to SV40 T antigen. These data suggest that specific immune tolerance to the product of an integrated viral oncogene may be induced, and is likely a reflection of the time in development at which the gene product first appears. Immune tolerance or responsiveness to the endogenous oncogene product may in turn play a role in the tumorigenic potential of such genes.